The Effect of Limb Muscle Explosive Power, Flexibility, and Achievement Motivation on Sickle Kick Performance in Pencak Silat Learning - Nurul Ihsan; Rudi Hanafi; Sepriadi Sepriadi; Ardo Okilanda; Suwirman Suwirman; Deby Tri Mario (OVS LLC, 2022)
Study Purpose. This study background is that the performance of the sickle kick in Pencak Silat learning is very important to improve the athlete's performance during the match, both when attacking and defending. The objective is to analyze the performance of the Pencak Silat sickle kick in terms of the quality of physical conditions (such as leg muscle explosive power and flexibility), and psychological elements (such as achievement motivation). Materials and methods. This study involved Pencak Silat athletes of Tangan Mas College, Padang, Indonesia. The participants who became the study sample were 30 male athletes aged 14-17 (athletes in the adolescent category). The sample selection was based on the sample criteria providing that participants had participated in regional level competitions and had attended training for at least 2 years. Data were obtained from several tests and measurements: leg muscle explosive power was measured using the Vertical Jump Test and then processed by the Lewis formula (nomogram). Flexibility was measured using the Side Split Test, achievement motivation was assessed using a questionnaire validated by experts, and a sickle kick performance was tested. The data obtained were analyzed using simple regression analysis and multiple regression analysis, followed by path analysis to calculate the coefficient value of each variable. Results. The data obtained were analyzed using structural model path analysis. Results: (1) there is an effect of leg muscle explosive power on the sickle kick performance by 21.59%; (2) there is an effect of flexibility on the sickle kick performance by 6.94%; (3) there is an effect of achievement motivation on the sickle kick performance by 9.74%; (4) there is an effect of leg muscle explosive power through achievement motivation on the sickle kick performance by 38.14%; (5) there is an effect of flexibility through achievement motivation on the sickle kick performance by 13.51%; and (6) there is a simultaneous effect of these variables by 51,41%. Conclusions. Based on the analysis of the three factors above, it was concluded that leg muscle explosive power is the dominant factor and needs to be taught and trained seriously. However, the other factors are no less important. Future studies are urgently needed to include other variables that affect the results of this study, as well as a wider number of samples to validate the results of this study.